PENGARUH SUPERVISI KEPALA SEKOLAH DAN PENGAWAS TERHADAP KREATIVITAS GURU SERTA DAMPAKNYA TERHADAP PRESTASI SEKOLAH - Mohamad Ali (DIALOGIKA, 2020)
This study aims to determine: 1) Supervision of high school principals; 2) Supervision of high school supervisors; 3) The creativity of high school teachers; 4) Student achievement; 5) the effect of supervision by high school principals on teacher creativity; 6) the effect of supervision of high school supervisors on the creativity of teachers; 7) the influence of supervision of high school principals and high school supervisors on the creativity of teachers; 8) The effect of the creativity of high school teachers on school performance in Majalengka Regency. This research method is a quantitative research method with descriptive and verification analysis techniques. Descriptive method using the calculation of frequency distribution, scoring and average value, while the verification method using path analysis. The sampling technique was taken by cluster proportional random sampling. Descriptive research results indicate that supervision carried out by principals and school supervisors is in the quite good category, while creativity and student achievement are in the quite up to good category. The results of the study verify that the supervision conducted by the school principal and school supervisor has a positive and significant effect on the teacher's creativity either partially or simultaneously. Teacher creativity has a positive and significant effect on student achievement